Development and numerical validation of an improved prediction model for wheel-soil interaction under multiple operating conditions. (October 2018) - Du, Yonghao; Gao, Jingwei; Jiang, Lehua; Zhang, Yuanchao
Highlights: A combination of equivalent-radius and bulldozing theory of lug effects. An improved method for lug effects according to the work conservation. An integrated prediction for wheel-soil interaction under multiple conditions. The model well predicts drawbar pull and torque but neglects sinkage's trend. Abstract: This paper presents the establishment and validation of an improved model predicting tractive parameters of a lugged wheel under multiple operating conditions. During the basic straight driving wheel-soil interaction, the common-used equivalent radius theory and the bulldozing theory are combined to calculate the lug effects referring the traditional theories of soil stress distribution, while the bulldozing effect is reconsidered according to the work conservation. On the basis of the further prediction under multiple conditions including the inclination in three degrees of freedom and the turning driving, the numerical model using the discrete element method under each operating condition is separately established. Under such circumstances, the validation and analysis are conducted differing in sizes and driving parameters of the wheel. It is indicated that the improved model displays the better reasonability and precision in predicting lug effects of a heavy off-road wheel. This model is mostly accurate and sensitive to the variation of parameters under straight and inclining driving conditions, but demands further correction during low slipping of the turning condition. Generally, the improved model in this paper focuses on the prediction of drawbar pull and driving torque, but lacks precision in the tendency of sinkage.